A review on clinical management of dental erosion - H Mazaheri; AA Khademi; F Keshani; F Keshani; M Khoroushi (Isfahan University of Medical Sciences, 2010)
Introduction: Dental erosion is chemical loss of tooth structure without the involvement of bacteria that is steadily spreading. At an advanced stage, the teeth become hypersensitive or the esthetics is affected. The aim of this review article is to introduce dental erosion, and giving information about its diagnosis, prevention and therapy.Review report: This review carried out by use of searching in various databases including Pubmed and ISI Web of Science from 1980 to 2010 on combination of the terms 'dental erosion, treatment and prevention.Results: The interplay of chemical, biological and behavior factors is crucial and helps to explain why some individuals exhibit more erosion than others. The erosive potential of erosive agents, including acidic drink or foodstuffs, depends on chemical factors. Instructions related to prevention involve use of chewing gum or rinsing with sodium bicarbonate, dental adhesive or fluoride containing materials.Discussion: As a result of the improvements in composite restorative materials and in adhesive techniques, it has become possible to rehabilitate eroded dentitions in a less invasive manner. Taking into account several investigations ceramic and composite materials show good durability under acidic conditions. Key words: Dental erosion, Treatment, Prevention